2020
DOI: 10.1016/j.bioelechem.2020.107540
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of delipidated human serum albumin on poly(pyrrole-2-carboxylic) acid film for the impedimetric detection of perfluorooctanoic acid

Abstract: TitleCovalent immobilization of delipidated human serum albumin on poly(pyrrole-2carboxylic) acid film for the impedimetric detection of perfluorooctanoic acid Article typeResearch Paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The elucidation of the molecular basis of the interaction between PFOA and hSA is expected to have implications for the development of superior hSA-based molecular receptors for diagnostic and biotechnological applications. 24 2 | RESULTS 2.1 | Overview of the crystal structure of hSA in complex with PFOA and myristic acid…”
mentioning
confidence: 99%
“…The elucidation of the molecular basis of the interaction between PFOA and hSA is expected to have implications for the development of superior hSA-based molecular receptors for diagnostic and biotechnological applications. 24 2 | RESULTS 2.1 | Overview of the crystal structure of hSA in complex with PFOA and myristic acid…”
mentioning
confidence: 99%
“…The peak current at +0.983 V decreased with increasing CV cycles, indicating that the polymer layer was successfully generated on the electrode surface. 48–51 As seen in Fig. 2(B), AuNPs coated on the ITO substrate had high peak currents, and these high peak currents illustrated that the AuNPs on the electrode surface accelerated the electron transfer kinetics of the redox probe.…”
Section: Resultsmentioning
confidence: 88%
“…The PFOS biosensor presented a wide range of linear detection between 5 and 500 nmol/L with a lowest detection limit of LOD = 1.6 nmol/L and high selectivity over different chemicals that co-exist with PFOS in micro-polluted water, which suggested that this biosensor might be implemented in real water monitoring. Moreover, an impedimetric biosensor for the detection of perfluorooctanoic acid (PFOA) was designed by the modification of a graphite screen printed electrodes (G-SPE) (Moro et al, 2020). This electrochemical biosensor was developed by the modification of a G-SPE with a covalently immobilized human serum albumin (hSA) as bioreceptor into pyrrole-2-carboxylic acid (Py-2-COOH) and PFOA was detected in range between 100 nmol/L and 5 μmol/ L. In addition, some other bioreceptors have been applied for the detection and monitoring of PFAs, such as DNA immobilized into Au/(Peroxide polypyrrole) electrode, which was applied for the detection of PFOA (Lu et al, 2011).…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%